Assessment of cerebral blood flow with magnetic resonance imaging in children with sickle cell disease: A quantitative comparison with transcranial Doppler ultrasonography. Issue 11 (14th October 2017) - Croal, Paula L.; Leung, Jackie; Kosinski, Przemyslaw; Shroff, Manohar; Odame, Isaac; Kassner, Andrea
Abstract: Introduction: Transcranial Doppler ultrasonography (TCD) is a clinical tool for stratifying ischemic stroke risk by identifying abnormal elevations in blood flow velocity (BFV) in the middle cerebral artery (MCA). However, TCD is not effective at screening for subtle neurologic injury such as silent cerebral infarcts. To better understand this disparity, we compared TCD measures of BFV with tissue‐level cerebral blood flow (CBF) using arterial spin‐labeling MRI in children with and without sickle cell disease, and correlated these measurements against clinical hematologic measures of disease severity. Methods: TCD and MRI assessment were performed in 13 pediatric sickle cell disease patients and eight age‐matched controls. Using MRI measures of MCA diameter and territory weight, TCD measures of BFV in the MCA [cm/s] were converted into units of CBF [ml min −1 100 g −1 ] for comparison. Results: There was no significant association between TCD measures of BFV in the MCA and corresponding MRI measures of CBF in patients ( r = .28, p = .39) or controls ( r = .10, p = .81). After conversion from BFV into units of CBF, a strong association was observed between TCD and MRI measures ( r = .67, p = .017 in patients, r = .86, p = .006 in controls). While BFV in the MCA showed a lack of correlation with arterial oxygen content, an inverse association was observed for CBF measurements. Conclusions: This study demonstrates that BFV in the MCA cannot be used as a surrogate marker for tissue‐level CBF in children with sickle cell disease. Therefore, TCD alone may not be sufficient for understanding and predicting subtle pathophysiology in this population, highlighting the potential clinical value of tissue‐level CBF. Abstract : Transcranial Doppler ultrasound (TCD) is an effective clinical tool for estimating bulk blood flow in large cerebral vessels. However, previous studies have shown poor correlation with microvascular cerebral blood flow. This study demonstrates, in a cohort of pediatric sickle cell disease patients and healthy controls, the physiological rationale that prevents TCD measures from being a reliable surrogate marker for tissue‐level cerebral blood flow.